2016
DOI: 10.9790/0837-2108052633
|View full text |Cite
|
Sign up to set email alerts
|

Sociology of Special Education: Teacher’s Support and Student’s Performance

Abstract: :-The present article focuses on the societal requirementsfor the learners with disabilities in inclusive schoolswhich may be socio-psychological and pedagogical practices. The process of inclusion starts with the assessment of attitudinal barrier of the learner by teachers/classmates in school/classroom settings demandsspecial and unique strategies, care and support for inclusion.To examine the phenomena of teacher"s support and student"s performance, five schools offering special education in Hyderabad and S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
0
0
Order By: Relevance
“…In the discussions surrounding special and inclusive education, this study examines the nature of special schools from the sociological perspectives of rights discourse, charity discourse, business discourse, social model, and medical model. (Bheenaveni, 2016) Studied "Sociology of Special Education: Teacher's Support and Student's Performance" and concluded that The process of inclusion starts with the assessment of attitudinal barrier of the learner by teachers/classmates in school/classroom settings demandsspecial and unique techniques, care and support for inclusion.In order to investigate the relationship between teacher support and student performance, five special education schools in the twin towns of Hyderabad and Secunderabad were selected for the study. The snow-ball sampling method was utilised to acquire 300 samples.…”
Section: Personal and Societal Implicationsmentioning
confidence: 99%
“…In the discussions surrounding special and inclusive education, this study examines the nature of special schools from the sociological perspectives of rights discourse, charity discourse, business discourse, social model, and medical model. (Bheenaveni, 2016) Studied "Sociology of Special Education: Teacher's Support and Student's Performance" and concluded that The process of inclusion starts with the assessment of attitudinal barrier of the learner by teachers/classmates in school/classroom settings demandsspecial and unique techniques, care and support for inclusion.In order to investigate the relationship between teacher support and student performance, five special education schools in the twin towns of Hyderabad and Secunderabad were selected for the study. The snow-ball sampling method was utilised to acquire 300 samples.…”
Section: Personal and Societal Implicationsmentioning
confidence: 99%